ANGPTL3 Is Involved in the Post-prandial Response in Triglyceride-Rich Lipoproteins and HDL Components in Patients With Coronary Artery Disease - Guo, Xin; Huang, Zhijie; Chen, Jin; Hu, Jiarui; Hu, Die; Peng, Daoquan; Yu, Bilian (Frontiers in Cardiovascular Medicine, 2022)
It is well-established that there exists an inverse relationship between high-density lipoprotein (HDL) cholesterol and triglyceride (TG) levels in the plasma. However, information is lacking on the impact of post-prandial triglyceride-rich lipoproteins (TRLs) on the structure of HDL subclasses in patients with coronary artery disease (CAD). In this study, the data of 49 patients with CAD were analyzed to evaluate dynamic alterations in post-prandial lipid profiles using nuclear magnetic resonance-based methods. An enzyme-linked immunosorbent assay was used to quantify the serum angiopoietin-like protein 3 (ANGPTL3). After glucose supplementation, the expression of hepatic ANGPTL3 was evaluated both in vitro and in vivo. Compared to fasting levels, the post-prandial serum TG level of all participants was considerably increased. Although post-prandial total cholesterol in HDL (HDL-C) remained unchanged, free cholesterol in HDL particles (HDL-FC) was significantly reduced after a meal. Furthermore, the post-prandial decrease in the HDL-FC level corresponded to the increase in remnant cholesterol (RC), indicating the possible exchange of free cholesterol between HDL and TRLs after a meal. Moreover, CAD patients with exaggerated TG response to diet, defined as TG increase >30%, tend to have a greater post-prandial increase of RC and decrease of HDL-FC compared to those with TG increase ≤30%. Mechanistically, the fasting and post-prandial serum ANGPTL3 levels were significantly lower in those with TG increase ≤30% than those with TG increase >30%, suggesting that ANGPTL3, the key lipolysis regulator, may be responsible for the different post-prandial responses of TG, RC, and HDL-FC.